Research on the Challenges and Approaches to Family Inheritance of Ethnic Traditional Sports Culture - Jiang, Caixia; Xia, Siyong; Qin, Hao (Quality in Sport, 2025)
Through the comprehensive use of literature, fieldwork, interviews, questionnaires, data analysis, logical reasoning and other methods, the study takes Shizhu County, Chongqing Municipality, one of the Tujia settlements in China, as an example to sort out the dilemmas that families currently face in the transmission of ethnic traditional sports culture, and to analyze the factors that lead to the dilemmas in the transmission of ethnic traditional sports culture. The results of the study show that there are the following dilemmas in the family inheritance of ethnic traditional sports culture in Shizhu County: alienation of children's ethnic traditional sports culture capital acquisition; lack of family integration of ethnic traditional sports culture; misunderstanding of the family's joint participation in ethnic traditional sports activities; lack of the main body of cultural inheritance, intergenerational inheritance stagnation; and lack of self-awareness of ethnic traditional sports culture. Based on the results of research on the relationship between the family environment and the inheritance of traditional ethnic sports culture, several experiences and insights have been presented: Strengthen the national cultural identity and establish the correct beliefs of parents; pay attention to the transformation of family capital and optimize the structure of capital distribution; create a supportive behavioral environment in the family to enhance the interaction between parents and children; promote the creation of the physical environment of traditional national sports and the precise implementation of the ground; integrate into classroom teaching and promote the "feeding" inheritance; strengthen social guidance to enhance the awareness of national sports; strengthen the platform construction to enhance the cultural atmosphere of traditional national sports. Integrate into classroom teaching to promote "feeding" inheritance; strengthen social guidance to enhance the awareness of national sports; and strengthen platform construction to enhance the cultural atmosphere of national traditional sports.